Patterns of use and dose optimization of renin-angiotensin system modulators among chronic heart failure patients with reduced ejection fraction in resource-limited settings: a multicenter cohort study - Sisay Sitotaw Anberbr; Samuel Berihun Dagnew; Getachew Yitayew Tarekegn; Fisseha Nigussie Dagnew; Zufan Alamrie Asmare; Teklie Mengie Ayele; Eskedar Dires Gebremeskel; Samuel Agegnew Wondm; Tilaye Arega Moges (Therapeutic Advances in Chronic Disease, 2025)
Background: Optimal use of renin-angiotensin system (RAS) modulators plays a crucial role in improving the outcomes for chronic heart failure (CHF) patients with reduced ejection fraction (rEF). Despite their established benefits, there is limited evidence regarding real-world prescribing patterns, dose optimization, and factors influencing RAS modulator use in this population. Objective: This study aimed to evaluate the patterns of use, dose optimization, and associated factors affecting the administration of RAS modulators among CHF patients with rEF at Public Comprehensive Specialized Hospitals (PCSHs). Design: A hospital-based, multicenter cohort study was conducted from February 1, 2020, to May 31, 2024, at PCSHs among CHF patients with rEF. Methods: A total sample size of 385 patients was determined using a systematic random sampling technique at the Northwest Ethiopian PCSHs during the study period. Data were collected from medical records and interviews using standardized questionnaires. Data analysis was performed using SPSS version 27.0, and binary logistic regression analysis was employed to identify factors associated with the use and optimization of RAS modulators. The study strictly adhered to the most recent guideline recommendations from the American Heart Association (2022) and the European Society of Cardiology (2021). Results: Of 385 patients, 263 (68.3%) were prescribed RAS modulators; however, only 86 (32.7%) of these patients were receiving an optimal dose. Predictors significantly associated with the use of RAS modulators included a duration of CHF with rEF of ⩾3 years (AOR: 1.79, 95% CI: 1.02–3.15), the presence of ischemic heart disease (AOR: 8.23, 95% CI: 4.23–16), hypertension (AOR: 2, 95% CI: 1.09–3.69), diabetes mellitus (AOR: 7.34, 95% CI: 1.48–36.34), chronic kidney disease (AOR: 4.35, 95% CI: 1.32–14.34), and a furosemide dose of ⩾40 mg (AOR: 0.26, 95% CI: 0.013–0.49). Regarding suboptimal RAS modulator dosing, significant predictors identified were age ⩾65 years (AOR: 2.83, 95% CI: 1.46–5.50), a previous history of hospitalization (AOR: 2.05, 95% CI: 1.07–3.95), the use of diuretics (AOR: 5.34, 95% CI: 2.73–10.44), a furosemide dose of ⩾40 mg (AOR: 3.88, 95% CI: 1.89–7.97), and CHF with rEF for ⩾3 years (AOR: 0.31, 95% CI: 0.16–0.63). Conclusions: The majority of CHF patients with rEF received suboptimal doses of RAS modulators, with only one-third receiving optimal therapy. This highlights a critical gap in treatment that must be urgently addressed. Targeted interventions are needed to identify and mitigate modifiable predictors contributing to suboptimal dosing, thereby improving therapeutic outcomes and reducing the burden of CHF with rEF.